2021
DOI: 10.4103/jmh.jmh_57_21
|View full text |Cite
|
Sign up to set email alerts
|

Role of Short-Term Estradiol Supplementation in Symptomatic Postmenopausal COVID-19 Females

Abstract: Background: Protective role of estrogen in COVID-19 was speculated once the epidemiological studies reported increased susceptibility of estrogen-deficient population – males and postmenopausal females to severe disease category and involvement of angiotensin-converting enzyme 2 receptors and renin–angiotensin– aldosterone system in pathophysiology. Materials & Methods: An open-label randomized controlled trial was planned to assess the efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The same study reported a similar Covid‐19 fatality risk for younger (premenopausal) women, irrespective of ERT; this probably reflects their higher endogenous estradiol (Seeland et al, 2020 ). Additionally, a small randomized trial ( n = 40) in hospitalized Covid‐19 postmenopausal females treated with oral estradiol supplementation (2 mg per day for 7 days) found faster recovery, while its small size ( n = 40) did not allow to identify a reduction in Covid‐19 fatalities (Seth et al, 2021 ). Larger cohorts are definitely required to assess the potential of prescribing estradiol to Covid‐19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The same study reported a similar Covid‐19 fatality risk for younger (premenopausal) women, irrespective of ERT; this probably reflects their higher endogenous estradiol (Seeland et al, 2020 ). Additionally, a small randomized trial ( n = 40) in hospitalized Covid‐19 postmenopausal females treated with oral estradiol supplementation (2 mg per day for 7 days) found faster recovery, while its small size ( n = 40) did not allow to identify a reduction in Covid‐19 fatalities (Seth et al, 2021 ). Larger cohorts are definitely required to assess the potential of prescribing estradiol to Covid‐19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In an open-label randomized controlled trial, it was shown that the use of estradiol valerate (2 mg per day for 7 days) with the standard care in estrogen-deficient postmenopausal women infected with mild and moderate COVID-19 caused a significant decrease in the D-dimer, lactate dehydrogenase (LDH), interleukin (IL)-6, and CRP on day 5 of the intervention [29]. In addition to this study, it has been shown that the use of oral contraceptive pills in 18-45-year-old women infected with COVID-19 significantly reduced the hospital attendance and had a significantly lower predicted COVID-19 [30].…”
Section: Discussionmentioning
confidence: 99%
“…As E2 administration is being considered as a supportive therapy in Covid-19 treatment [ 25 , 26 ] it may be of interest that E2 also influences the circadian system, which in turn regulates the expression of hundreds of clock-controlled genes. The finding that ACE2 and TMPRSS2 mRNA exerted a low-amplitude rhythm in animals exposed to E2 brings up the idea that the daily pattern in their expression can be modified under conditions of rhythmic E2 administration.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that in women above 50 years of age, EHT reduced the risk of fatality from Covid-19 by more than 50% [ 25 ]. Similarly, short-term oral administration of E2 decreased the time to viral clearance in Covid-19 patients [ 26 ]. Although ACE2 levels were not monitored in these studies, it has been demonstrated previously that E2 treatment increased ACE2 activity in the plasma [ 27 ].…”
Section: Introductionmentioning
confidence: 99%